If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + x + -12 = 63 Reorder the terms: -12 + 15x + x = 63 Combine like terms: 15x + x = 16x -12 + 16x = 63 Solving -12 + 16x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 16x = 63 + 12 Combine like terms: -12 + 12 = 0 0 + 16x = 63 + 12 16x = 63 + 12 Combine like terms: 63 + 12 = 75 16x = 75 Divide each side by '16'. x = 4.6875 Simplifying x = 4.6875
| 2+x+19=2x+33 | | 2x+5(x-4)=8 | | 10b+10+2b=-10+8b | | -6x-x=20 | | 19x-(8x-4)=92 | | (X+78)x+41=95 | | -2=b-11 | | 126=-7(-5a-3) | | 3(x+2)=2(2+x) | | 2(-6-5x)=68 | | 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) | | (X+41)+x+78=95 | | 7+2[m-4]=3 | | 90=(3x+13)(5x-7) | | 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 | | 3h+2h+9=54 | | 13=5x+1-3x | | .20*5000= |